2017
DOI: 10.1002/adma.201703062
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Quantum Anomalous Hall Effect by Magnetic Codoping in a Topological Insulator

Abstract: The quantum anomalous Hall (QAH) effect, which has been realized in magnetic topological insulators (TIs), is the key to applications of dissipationless quantum Hall edge states in electronic devices. However, investigations and utilizations of the QAH effect are limited by the ultralow temperatures needed to reach full quantization-usually below 100 mK in either Cr- or V-doped (Bi,Sb) Te of the two experimentally confirmed QAH materials. Here it is shown that by codoping Cr and V magnetic elements in (Bi,Sb) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
123
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 37 publications
4
123
0
1
Order By: Relevance
“…Furthermore, in the host TIs (Sb 1−x Bi x ) 2 Te 3 , the carrier type can be widely tuned from p to n with an increase of x [21][22][23]. Especially, V-doped (Sb,Bi) 2 Te 3 is a hard ferromagnet exhibiting a larger coercive field and higher Curie temperature compared to the Cr-doped cases but the working temperature of the QAHE is still very low although extensive efforts have been made to improve it by modulation doping or co-doping methods [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the host TIs (Sb 1−x Bi x ) 2 Te 3 , the carrier type can be widely tuned from p to n with an increase of x [21][22][23]. Especially, V-doped (Sb,Bi) 2 Te 3 is a hard ferromagnet exhibiting a larger coercive field and higher Curie temperature compared to the Cr-doped cases but the working temperature of the QAHE is still very low although extensive efforts have been made to improve it by modulation doping or co-doping methods [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The anomalous Hall effect (AHE) exits in the absence of external magnetic field, and appears due to internal magnetisation. [28][29][30][31][32][33][34][35] Such effect can also be found in two dimensional hexagonal lattices [36,37], closely related to the models we consider here. Recent experiments have reported large AHE in topological insulators with proximity induced magnetism.…”
mentioning
confidence: 76%
“…Moreover, the magnetically doped (Bi,Sb) 2 Te 3 TI and CdSe normal insulator layers in the superlattice structure has been successfully grown by molecular beam epitaxy [33]. It has been shown that the coercive field of magnetic TI in each layer can be controlled by mixing the dopants Cr and V at varied ratios [66]. In fact, a magnetic TI bilayer with different dopants ratios was driven to the opposite magnetization by sweeping the magnetic field in a recent experiment [67].…”
mentioning
confidence: 99%